Infusion: catalyzing progressive design strategies in the Knobtown District - O'Keefe, Zachary Scott (Kansas State University, 2012)
Sustainable landscape design is generally understood in relation to three principles—ecological health, social justice, and economic prosperity. However, people have neglected to recognize the significance of their impact on the environment. The real conflict begins to address our relationship with the environment and how we attempt to reconnect and reverse centuries of environmental degradation. As a society, we lie at the intersection of the past and the future, presenting us the opportunity to think organically. Harboring values much different from post-industrial thinking, organic values work with nature rather than against it. However, most contemporary processes are not organic in nature. Rather they are products of our isolated way of thinking; a limited form of consciousness that arrogantly declares that we are the greatest intelligence on Earth. This consciousness has taught us that for our survival, it is our duty to subdue nature, relating to it as a resource for implementing how and what our minds invent. We have learned to relate to nature as a commodity rather than respect it as our community. Infusion seeks to establish this connection by creating a Transit-Oriented Development in the Knobtown District that uses the power of aesthetics to promote and inspire educational exploration, cultural expression, and ethical revelation of sustainable design. Supporting this solution is a four-part foundational framework that identifies specific design principles that are envisioned to improve the way we relate to our environment through aesthetic eminence educational exploration, cultural expression and ethical revelation. The conceptualized framework is structured to be adaptable for many design situations becoming a foundation for the way in which we design and interact with form and space. In its final state, Infusion communicates the significance of these essential design principles and how the new Knobtown District can become an important part of the Rock Island Corridor.
Keywords: Creating Sustainable Places; Transit-Oriented Development; Aesthetics; Landscape Architecture (0390)